Taking off : - Fesler, Susan Hancock (McGraw-Hill, 2003)
Taking Off is a four-skills, standards-based program for low-beginning adult ESL students. Picture dictionary art pages teach life skills vocabulary in a clear and visual way. The gradual pace of the course instills confidence in students as they establish a solid foundation in the basics of English.